Pengaruh Karakteristik Individu dan Faktor-Faktor Pekerjaan Terhadap Motivasi (Studi Pada Karyawan CV. Bintang Timur Semarang) - Setiawan, Andy; Bodroastuti, Tri (Jurnal Kajian Akuntansi dan Bisnis, 2012)
This study aimed to determine the influence of individualcharacteristics and work factors on motivation of employees of CV. Bintang TimurSemarang. In this study, the population was CV. Bintang Timur employees totaled 50people, including leaders, the entire population was sampled. The analytical tool used inthis research was multiple linear regression. The results showed that on the basis of thepartial test of the hypothesis with t test results obtained X1 = 3.837; X2 = 15.712; X3 =7.447; X4 = 2.944; X5 and X6 = 5.436 = 4.869 and 2.012 t table that was in the area ofreject Ho, means there was significant influence of motivation, job satisfaction, stresslevels, physical work conditions, compensation systems and design work on motivation.While on the test results obtained F value, F = 522.971 > F table 3.232 was in the areaof reject Ho, meaning that there was significant influence of individual characteristicsand work factors on motivation. The coefficient of determination of both independentvariable was 98.50%, it means that the variation of these two variables in explaining themotivation for the remaining 98.50% (100% - 98.50%) = 1.50% was explained by othervariables that were not mentioned in the study.Keywords: Individual Characteristics, Work Factors and Motivation